2022
DOI: 10.3390/ijms23169440
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Apamin-Mediated Nano-Lipidic Carrier Potentially Enhances the Cytotoxicity of Ellagic Acid against Human Breast Cancer Cells

Abstract: Ellagic acid has recently attracted increasing attention regarding its role in the prevention and treatment of cancer. Surface functionalized nanocarriers have been recently studied for enhancing cancer cells’ penetration and achieving better tumor-targeted delivery of active ingredients. Therefore, the present work aimed at investigating the potential of APA-functionalized emulsomes (EGA-EML-APA) for enhancing cytototoxic activity of EGA against human breast cancer cells. Phospholipon® 90 G: cholesterol molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Doxil, the first US Food and Drug Administration (FDA)-approved chemotherapeutic nanosystem to be used therapeutically, contains doxorubicin (DOX). The PEGylated DOX liposomal formulation extends circulation time and prevents premature removal of the nanoformulation . For dual targeting, i.e.…”
Section: Therapeutic Interventions Involving Nanocarriers For Managem...mentioning
confidence: 99%
See 4 more Smart Citations
“…Doxil, the first US Food and Drug Administration (FDA)-approved chemotherapeutic nanosystem to be used therapeutically, contains doxorubicin (DOX). The PEGylated DOX liposomal formulation extends circulation time and prevents premature removal of the nanoformulation . For dual targeting, i.e.…”
Section: Therapeutic Interventions Involving Nanocarriers For Managem...mentioning
confidence: 99%
“…Flow cytometric tests verified the improved cell penetration of the NLCs against the BT-474 cell line . Ellagic acid (EGA) is commonly used to prevent and treat cancer . A plethora of researchers have reported that surface-functionalized nanocarriers have been evaluated in tumor-targeted delivery of anticancer drugs .…”
Section: Therapeutic Interventions Involving Nanocarriers For Managem...mentioning
confidence: 99%
See 3 more Smart Citations